Consumers' Attitude Towards Online Shopping : The Affecting Of Recommendation Agents - Mas'od, Siti Nor Rafidah (UTeM, 2016)
Online shopping is the use of technology for better marketing performance. The retailers are developing strategies to meet the demand of online shoppers they are busy in studying consumer behavior in the field of online shopping, to see the consumer attitudes towards online shopping. Therefore, the researcher has decided to study consumer’s attitudes towards online shopping and specifically studying the factors influencing recommendation agent towards consumers’ decision making to shop online. The respondents selected for the research is lecturers from KPTM Batu Pahat. The sample size selected for this research is 90 and the researcher used convenience sampling technique. The results of the study indicate that recommendation agents have a significant impact on consumer decision making. As expected, the use of the recommendation agents reduces consumers’ effort to search for products information. The findings indicated that among the four factors for this research have shown the most attractive and influencing factor for online shoppers is convenience, following security the second most influencing and thirdly time saving. Results have also showed that Website Design/ concerns are very important to how consumer get the information about product that they want to buy. Hence, the effectiveness of recommendation agents helps the consumers to get information and comparison.